1998
DOI: 10.1002/(sici)1096-9861(19980615)395:4<440::aid-cne2>3.3.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Transmitter identification in neurons involved in male copulation behavior in Lymnaea stagnalis

Abstract: In this paper, we have mapped the cellular localization of various transmitters onto the central neurons which are involved in male copulation behavior in Lymnaea stagnalis, by combining retrograde tracing with immunocytochemistry and in situ hybridization. Evidence is provided that neurons which were backfilled from the penis nerve, the sole nerve to innervate the male copulatory organ, synthesize a multitude of neuropeptides (APGWamide, Lymnaea neuropeptide tyrosin [LNPY], conopressin, pedal peptide, SEEPLY,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…We confirm the presence of this peptide in the HP neurons only. This earlier immunocytochemical study also showed that anti-DEILSR and anti-LIP ( Lymnaea inhibitory peptide) are mutually exclusive in the backfilled neurons of the right parietal ganglion, suggesting that at least some of the silent, DEILSR-negative parietal cells with projections into only the penis nerve are LIP-containing cells (de Lange et al 1998a ). However, our MALDI-TOF-MS data do not support this hypothesis since they did not confirm the presence of LIP in the nonHP neurons.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…We confirm the presence of this peptide in the HP neurons only. This earlier immunocytochemical study also showed that anti-DEILSR and anti-LIP ( Lymnaea inhibitory peptide) are mutually exclusive in the backfilled neurons of the right parietal ganglion, suggesting that at least some of the silent, DEILSR-negative parietal cells with projections into only the penis nerve are LIP-containing cells (de Lange et al 1998a ). However, our MALDI-TOF-MS data do not support this hypothesis since they did not confirm the presence of LIP in the nonHP neurons.…”
Section: Discussionmentioning
confidence: 90%
“…Male mating in the pond snail, Lymnaea stagnalis , was the focus of many multidisciplinary studies aimed at getting a deep insight into the regulation of this behavior. It has been studied in great detail and at different levels: behavioral (van Duivenboden 1984 ; de Boer et al 1996 ; Koene and Ter Maat 2005 , 2007 ), electrophysiological (de Boer et al 1997 ), biochemical (Li et al 1992 ; 1995 ), immunohistochemical (de Lange et al 1997 , 1998a , b ) and functional (van Golen et al 1995a , b ). Male mating is a complex behavior consisting of a series of stereotypic stages, movements and decisions that reflect an accurate communication between two partners that both have the ability to be male or female (van Duivenboden 1984 ; Koene and Ter Maat 2005 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations